Suitability Evaluation of Mudstone of Injana Formation for Dam Filling Materials in TaqTaq area/Erbil/Iraq - Fahad Jamal Suhael; Amera Ismail Hussain (Tikrit Journal of Pure Science, 2020)
The research aims to study some geotechnical properties for mudstone of  Injana Formation  in the eastern part of Erbil city, to determine their suitability as filling  materials in the dams. Nine samples representing the study area were sampled. From the results of  petrophysical tests, the liquid limit and the plasticity index were found to be within the limits of the Iraqi standard, the values of the liquid limit range between  (39.26-44.2)%. The plasticity index ranges between (14.96-19.82). The grain size distribution analysis shows the applicability of the zone C for Nine samples.Total soluble salts (T.S.S). Ranging from (1.04 -4.81) The gypsum contains between (0.02-0.09)%. It conforms to the Iraqi standard specification where the results of the samples (1)(2)(4)(5) suitable for the filling  materials in the dams but the (3)(6)(7) (8)(9) samples unsuitable